Analisis Implementasi Matriks dalam Estimasi Laju Pertumbuhan Populasi Wanita - Wijaya, Ulfia Imelda; Nisfulaila, Intan (Jurnal Riset Mahasiswa Matematika, 2023)
Leslie matrix is a growth matrix used to estimate the growth rate of a population. Through the population growth rate, information can be obtained whether the growth tends to increase, decrease, or stabilize. The general form of the Leslie matrix is a square matrix in which the first-row entries contain values of female fertility rate , the subdiagonals contain values of female survival rate , and entries other than in the first row and sub diagonals are zero. This research is to determine the implementation of the Leslie matrix in estimating the female population growth rate in Situbondo Regency 2023 and its analysis. The stages of this research began with presenting the Leslie matrix population growth model for the next three years. The second stage is to determine the age class interval. Next, determine the initial age distribution vector. The fourth and fifth stages, respectively, are calculating the  and the  value. The next step is constructing the Leslie matrix. The seventh stage is to calculate the estimated female population. The eighth stage is determining the eigenvalue and ends with determining the dominant eigenvalue. Based on the results of the research that has been done, it is obtained that the estimated female population in Situbondo Regency 2023 tends to decrease with the acquisition of a dominant eigenvalue that is less than one. That information can be taken into consideration by the government in formulating population-related policies.